Optimal Siting, Sizing and Operation of Active Power Line Conditioners (APLCs) in Unbalanced Distribution Networks Embedded with Rooftop PVs for Harmonic Mitigation and Reactive Power Compensation - Kazemi, Saeed (Curtin University, 2022)
This thesis aims to address power quality problems by proposing an approach that uses APLCs in unbalanced smart distribution networks. The goal is to improve the total voltage harmonic distortion (THDv), regulate the voltage and reduce the total loss at all buses with the minimum number and rating of APLCs. A particle swarm optimisation (PSO) algorithm is employed for the optimisation and a Newton-Raphson-based unbalanced harmonic load flow algorithm is developed as a back bone of calculations.